Hungarian Monitoring, 21 October 1988 . [Magyar rádiófigyelő], 1988. október 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Rakowski in Moscow - New draft Soviet constitution - Sakharov can travel to the US - Warsaw workers' negative experiences of Polish economic mechanisms - Genscher-Dumas talks play a decisive role in renewing French diplomacy - F. and I. Marcos charged with fraud and embezzlement in the US Domestic Affairs: - Budapest Police HQ denies permission to Alliance of Young Democrats (Fidesz) and other groups wanting to hold march commemorating October 23, 1956 - Patriotic Popular Front: preliminary ban on public meetings is wrong - National Council of Trade Unions (SZOT) presidency in session - Government creates social committee to check Gabčíkovo-Nagymaros project - Relations between Romanian minorities and the press Economy: - Imre Pozsgay's opinion on property reform - Planned Economy Committee in session Külpolitika: - Rakowski Moszkvában - Az új szovjet alkotmány tervezete - Az Egyesült Államokba utazhat Szaharov - A varsói munkások negatív tapasztalatai a lengyel gazdasági mechanizmussal - A Genscher-Dumas megbeszéléseknek döntő szerepük van a francia diplomácia megújulásában - Csalás és sikkasztás miatt vádat emeltek F. és I. Marcos ellen az Egyesült Államokban Belpolitika: - A BRFK nem engedélyezi a FIDESZ és más csoportok október 23-i megemlékező felvonulását - HNF elnökség: helytelen a gyülekezések előzetes betiltása - SZOT elnökségi ülés - A kormány a bős-nagymarosi beruházást ellenőrző társadalmi bizottságot hoz létre - A román kisebbség és a sajtó viszonya Gazdaság: - Pozsgay Imre véleménye a tulajdonformákról - Tervgazdasági Bizottság ülése